2021
DOI: 10.3897/folmed.63.e54750
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Spinal Schwannomas and Neurofibromas – a Review

Abstract: Tumours arising from the spinal nerve roots are more common in men between the third and fourth decades of life, located mainly in the intradural space of the lumbar region. The clinical symptoms of spinal schwannomas and neurofibromas are similar and depend on the location of the tumour and its relationship to the spinal cord and nerve roots. The pain (radiculalgia and/or vertebralgia) is the earliest symptom, followed by sensory deficit, while motor deficits and sphincter disorders are late symptoms. Magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In line with this, authors such as Apostolov have highlighted the importance of complete tumor resection to promote full neurological recovery [12]. There is a consensus that GTR can be safely and effectively achieved for most nerve sheath tumors and that GTR reduces the risk of tumor recurrence [3,9,12,24,25]. In our cohort, GTR was achieved in 83% of cases, which is similar to the previously reported GTR rate of 80-90% [2,3,5,6,14].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In line with this, authors such as Apostolov have highlighted the importance of complete tumor resection to promote full neurological recovery [12]. There is a consensus that GTR can be safely and effectively achieved for most nerve sheath tumors and that GTR reduces the risk of tumor recurrence [3,9,12,24,25]. In our cohort, GTR was achieved in 83% of cases, which is similar to the previously reported GTR rate of 80-90% [2,3,5,6,14].…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, since neurological symptoms are mainly reflective of nerve root or spinal cord compression, only patients with symptomatic compression can improve. In line with this, authors such as Apostolov have highlighted the importance of complete tumor resection to promote full neurological recovery [12]. There is a consensus that GTR can be safely and effectively achieved for most nerve sheath tumors and that GTR reduces the risk of tumor recurrence [3,9,12,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the tumor location, it would be considered atypical if it were intramedullary, as such a location according to Koeller and Shih is observed in only 1.1 % of cases of spinal schwannomas [ 2 ]. The lumbar location of spinal schwannomas in their study was observed from 25.6 % to 60 % of cases, which according to Jinnai et al, is due to the anatomical characteristics of the spinal nerves, which travel a greater distance in the region of the cauda equina [ 4 , 5 ]. In this regard, the localization of the schwannoma described by Lim D.-J.…”
mentioning
confidence: 99%